Some ways of translating Abai’s metaphors (Herald of Journalism, 2020)
The paper tells about an actual problem of linguistics – a metaphor and its role in a poetic composition of the work. The paper gives special attention to individual author’s metaphors (actuallypoetic ones), concep tualthematic world picture in the light of individualauthor metaphor. Individualauthor metaphors of the great Kazakh poet Abai are studied    in the reality of concept spheres. On the material of Abai’s poetic texts the meaning of individualauthor metaphors is revealed. Diverse methods, ways and keys of metaphor translation, which were described by different scholars and researchers, are given in this article.
Keywords: metaphor, individualauthor metaphor, image and poetic metaphor, concept spheres, translation.